A\crypto-Dravidian origin for the nontribal communities of South India based on human leukocyte antigen class I diversity - R. Thomas, S. B. Nair & M. Banerjee (Journal compilation 2006, 2006)
The Dravidian communities are considered to be the original inhabitants of India, now restricted to South India. The southern most state, Kerala, is socio-culturally stratified into Hindus, Muslims and Christians on the basis of religion. The origin of these religious communities in Kerala is considered to be unique in comparison with that in other parts of the country. These communities were later influenced by the hierarchical caste structure established by the Hindu Brahmins. In the present study, we compared six nontribal (Namboothiri, Nair, Ezhava, Pulaya, Malabar Muslim and Syrian Christian) communities belonging to the major religious groups in Kerala (Hindu, Muslim and Christian) based on the human leukocyte antigen (HLA)-A, -B and -C diversity. Our aim was to understand the genomic substructuring associated with the changing social scenario in various caste and religious groups and compare it with the Dravidian tribal and other world populations. The present study reveals that the HLA diversity of the Dravidian communities is very distinct from that in the other world populations. It is obvious that the nontribal communities of Kerala display a greater Dravidian influence, but traces of genetic admixture with the Mediterranean, western European, centralAsian and East Asian populations can be observed. This characterizes the crypto-Dravidian features of the nontribal communities of Kerala. Demic diffusion of thelocal progressive communities with the migrant communities may have given rise tocrypto-Dravidian features among the nontribal communities of Kerala.